2021
DOI: 10.1021/acs.jmedchem.1c01174
|View full text |Cite
|
Sign up to set email alerts
|

Development of Potent and Selective Agonists for Complement C5a Receptor 1 with In Vivo Activity

Abstract: The anaphylatoxin C5a is a complement peptide associated with immune-related disorders. C5a binds with equal potency to two GPCRs, C5aR1 and C5aR2. Multiple C5a peptide agonists have been developed to interrogate the C5a receptor function but none show selectivity for C5aR1. To address these limitations, we developed potent and stable peptide C5aR1 agonists that display no C5aR2 activity and over 1000-fold selectivity for C5aR1 over C3aR. This includes BM213, which induces C5aR1-mediated calcium mobilization a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 55 publications
0
13
0
Order By: Relevance
“…Additionally, the loss of β-arrestin 2 recruitment in a previous study was shown to be due to L P6 A substitution in BM213. 36 Our results indicated that the distance between position P6 in the agonist and the TM2–ECL1–TM3 or IWI region in C5aR1 contributes to receptor-biased signaling. Therefore, to investigate the biased mechanism by which C5aR1 senses BM213, an additional cryo-EM structure of the BM213-bound C5aR1–G i protein complex was solved at a 2.9 Å resolution (Fig.…”
Section: Resultsmentioning
confidence: 54%
See 3 more Smart Citations
“…Additionally, the loss of β-arrestin 2 recruitment in a previous study was shown to be due to L P6 A substitution in BM213. 36 Our results indicated that the distance between position P6 in the agonist and the TM2–ECL1–TM3 or IWI region in C5aR1 contributes to receptor-biased signaling. Therefore, to investigate the biased mechanism by which C5aR1 senses BM213, an additional cryo-EM structure of the BM213-bound C5aR1–G i protein complex was solved at a 2.9 Å resolution (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…To further investigate these findings, we prepared several derivatives of BM213 with modifications at the P7 position. As the original BM213 study reported, conversion of d -alanine to l -alanine at P7 substantially reduced downstream signaling, 36 while another pharmacological analysis suggested increased aromaticity at this position attenuated C5aR1 activity. 39 Our functional assays revealed that the BM213 P7- d I, BM213 P7- d L , and BM213 P7- d F derivatives, which have bulkier side chains at P7, exhibited a moderate influence on the G i protein signaling; meanwhile, C5aR1 stimulated with l -residues at the P7 position markedly impaired the activation efficacy (Supplementary information, Fig.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…A series of mutagenesis studies, coupled with functional assays, have suggested that binding of C5a with C5aR1 involves an interface between the core region of C5a with the N-terminus and extracellular loop 2 (ECL2) of C5aR1, and a second interface between the carboxyl-terminus of C5a with the extracellular pocket of the receptor [13][14][15][16] . In addition to C5a, several peptide ligands derived from, and modified based on the carboxyl-terminus sequence of C5a, have been described as potent agonists for C5aR1, albeit with relatively lower affinities [16][17][18][19][20][21] . Of these, a hexapeptide referred to as C5a pep is particularly interesting as it behaves as a functionally-biased agonist compared to C5a in terms of transducer-coupling and cellular responses 11 .…”
Section: Introductionmentioning
confidence: 99%